Prominent Activation of the Putamen during Essential Palatal Tremor: A Functional MR Imaging Case Study - Haller, S.; Winkler, D.T.; Gobbi, C.; Lyrer, P.; Wetzel, S.G.; Steck, A.J. (American Journal of Neuroradiology, 2006)
Summary: Palatal tremor (PT), also known as palatal myoclonus, is defined by short rhythmic contractions of the palatal musculature. Functional MR imaging (fMRI) revealed prominent bilateral neuronal activation in the putamen associated with essential palatal tremor (EPT) in a 41-year-old man. This implies a central role of the putamen in EPT, most likely as a consequence of diminished inhibition in an afferent pathway. Because fMRI primarily detects activations, dysfunctional areas remain obscure. The present functional study complements previous pathologic studies, which associated PT with lesions to dentate nucleus, red nucleus, and the inferior olive (Guillain-Mollaret triangle).